Review of opportunities and challenges represented by big data for fintech in Malaysia - Ibrahim Ahmed, Ibrahim Nasreldin; Abdullah, Lili Marziana; Mohd Nor, Rizal (Kulliyyah of Information and Communication Technology International Islamic University Malaysia, 2023)
This paper explores the potential of big data for driving economic growth and innovation within the fintech sector in Malaysia. By using systematic literature review, it investigates the opportunities of big data in the fintech sector and its current utilisation in Malaysia. Firstly, the paper will outline current trends in fintech within the Malaysian context. This will include examining the current state of big data utilization, prevalent initiatives, and current industry players. Secondly, it will identify challenges for fintech development by exploring technological, organisational, and environmental factors that might affect the utilisation of big data in Malaysia. Finally, it will suggest approaches for organisations to adopt in overcoming these challenges. The paper hopes to enrich the understanding of the opportunities and challenges for big data in fintech in Malaysia and the ways it can contribute to the domestic economy.